2020
DOI: 10.3390/ani10101773
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Avium Paratuberculosis: A Disease Burden on the Dairy Industry

Abstract: Mycobacterium avium paratuberculosis is responsible for paratuberculosis or Johne’s disease in cows, having economic impacts on the dairy industry and a prevalence rate exceeding 50% in dairy herds. The economic burden of Johne’s disease relates to decreased milk production and costs of disease prevention, treatment, and management, while having an economic impact on dairy producers, processors, consumers, and stakeholders of the dairy industry. Determining the true economic impact of the disease is difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 56 publications
0
44
0
3
Order By: Relevance
“…These categories are based on the presence and severity of clinical signs, the rate of environmental shedding and the likelihood of detection with current MAP diagnostic methods [ 4 ]. Animals that are infected with MAP, but have no evidence of disease and cannot be detected with current diagnostic methods, are said to be in the silent stage [ 5 ]. Subclinical animals show an immune response, shedding low but infectious levels of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These categories are based on the presence and severity of clinical signs, the rate of environmental shedding and the likelihood of detection with current MAP diagnostic methods [ 4 ]. Animals that are infected with MAP, but have no evidence of disease and cannot be detected with current diagnostic methods, are said to be in the silent stage [ 5 ]. Subclinical animals show an immune response, shedding low but infectious levels of the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…As there are no effective cures yet developed for JD, these control programmes are employed in order to try and eradicate the disease. Furthermore, the current vaccines for MAP compromises the diagnosis of bovine tuberculosis in cattle [ 5 , 51 ]. JD vaccination programmes have been implemented in several countries including the USA, which previously used the commercially available vaccine Mycopar®, but have now been discontinued (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Paratuberculosis (PTB), also known as Johne's disease, is a contagious bacterial disease typical of domestic and wild ruminants, characterized by chronic progressive granulomatous enteritis [1], with consequent severe deterioration of the general conditions of animals and economic losses [2]. Although the disease was first reported in cattle, the infection has also been identified worldwide among small ruminants [3].…”
Section: Introductionmentioning
confidence: 99%
“…JD affects domestic animals such as farm deer, sheep, and dairy cattle. The prevalence of JD in cattle in Australia, New Zealand, Europe, and the United States was estimated to range from 10 to 60% (1)(2)(3)(4). United States Department of Agriculture (USDA) reported that 68.1% of dairy herds in the US are contaminated with MAP, and the most recent report estimated that the actual herd-level prevalence of MAP was higher than 90% (5).…”
Section: Introductionmentioning
confidence: 99%
“…Economic loss caused by JD in dairy herds is mostly due to the reduced milk production and premature culling of JD-affected cattle (7). In the USA, JD causes an estimated annual loss of $220 million to the agricultural economy (4,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%